Book about Animals - Merrill, Rufus, 1803-1891 (Salt Lake City, UT : Project Gutenberg, 2004)
"Book about Animals" by Rufus Merrill is a descriptive work likely written in the mid-19th century. This book serves as an informative publication focusing on various animals, offering insights into their characteristics, habitats, and behaviors. It is geared towards educating readers about the animal kingdom in an engaging manner. In "Book about Animals," the author highlights a range of creatures, providing succinct descriptions of their physical attributes and lifestyles. Merrill covers notable species such as the elephant, known for its size and gentle nature; the Ourang Outang, a large ape adept at tree climbing; and the Opossum, recognized for its unique pouch for carrying young. The book further explores the antelope's elegance, the rabbit's domestic habits, and the hunting practices of the polar bear. Each entry emphasizes the animals' distinctive features and behaviors, creating a vivid picture of the diverse life forms within the animal kingdom while aiming to promote appreciation and understanding of wildlife. (This is an automatically generated summary.)
The elephant -- The ourang outang -- The oppossum -- The common antelope -- The rabbit -- The musk deer -- The polar bear.
Release date is 2004-01-01
Produced by Ben Courtney and PG Distributed Proofreaders
Keywords: Animals -- Juvenile literature